Desenvolvimento e análise de protocolos de comunicação serial para integração com dispositivos ESP32 - Almeida, Elias Alexander Santos de (Brasil, 2024)
In the current context of increasing demand for efficient solutions in automation and the Internet of Things (IoT), the ESP32 microcontroller plays a crucial role in projects such as home automation, robotics, and electronic systems. In many of these projects, robust operating systems like Linux are used to ensure efficient communication between the ESP32 and other software components, optimizing control and data exchange between devices and larger systems. This work proposes the development of a driver for the Linux kernel, enabling integration with the ESP32 microcontroller, which controls sensors and actuators in an automation environment. The project’s focus is on creating a system that allows the control of devices such as LEDs and temperature and humidity sensors via serial communication, as well as integration with a Telegram bot to facilitate remote control. The firmware developed for the ESP32 was configured to interact with the Linux system, being able to receive commands and return data through serial communication. Additionally, the communication with the Telegram bot allowed remote interaction, offering a simple and efficient interface for controlling actuators and reading sensor data. During the development, changes were made to the kernel driver to support this communication, ensuring complete integration between hardware and software. The project met the proposed objectives, providing an efficient and flexible solution for embedded system automation, with potential for expansion to various other applications.